The Big Picture. - Neumann, Peter G. (Communications of the ACM, 2004)
It is informed that system and network security, reliability, survivability, interoperability, predictable behavior, and other important attributes are for the most part not receiving enough dedicated attention. The computer-communication infrastructures are riddled with flaws. In the absence of really serious attacks, governments and system developers seem to have been lulled into a false sense of security. Thus far, neither proprietary nor source-available system developers are sufficiently militant in satisfying critical needs. In mass-market software, the patch mentality seems to have won out over well-designed and well-implemented systems. Despite past recognition of the pervasiveness of serious vulnerabilities, critical national infrastructures are still vulnerable to attacks and accidental collapses. For example, massive power outages are still not unusual, despite supposed improvements. It is also opined that the U.S. university curricula in software engineering and trustworthy systems seems to be less responsive to needs of critical systems than in certain other countries. Furthermore, significant decreases have recently been reported in U.S. undergraduate computer-science student enrollment numbers, perhaps because of a noticeable reduction in foreign students. This situation has serious long-term implications worldwide.